Technical Quality of Root Fillings Performed by Undergraduate Students: A Radiographic Study - Tatjana Vukadinov; Larisa Blažić; Ivana Kantardžić; Tijana Lainović (The Scientific World Journal)
Aim. The aim of this study was to evaluate the radiographic technical quality of endodontic treatment performed by undergraduate students at the School of Dentistry, Faculty of Medicine, University of Novi Sad, Serbia. Materials and Methods. Electronic records of 220 patients treated by final-year undergraduate students during the school year 2011/2012 were examined, and the final sample consisted of 212 patients, 322 teeth, and 565 root canals. The criteria for overall radiographic adequacy of root canal fillings were defined as the presence of adequate length and density and absence of iatrogenic errors (ledge, fractured instrument, untreated canal, and apical transportation). Chi-square test was used to determine statistical significance between different parameters. Results. Adequate root canal fillings were found in 74.22% of the teeth. The percentage of root fillings with adequate length and density was 89.73% and 92.6%, respectively. Fractured instruments and ledges were present in 16 root canals (2.8%), while the presence of missed canal and apical transportation was observed in 2 cases, each (0.3%). Conclusions. Overall, the technical quality of root canal fillings performed by undergraduate students was satisfactory.